The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3109/14992027.2010.532512
|View full text |Cite
|
Sign up to set email alerts
|

Auditory steady state responses recorded in multitalker babble

Abstract: The presence of babble significantly reduced the ASSR detection rate and ASSR amplitude for NH subjects, but had minimal effect on ASSRs for HI subjects. In addition, babble enhanced ASSR amplitude at high stimulus levels. ASSR detection rate and ASSR amplitude recorded in quiet and babble were significantly correlated with word recognition performance for NH and HI subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…There are several reasons why contralateral suppression of ASSRs may be a promising tool for studying MOC activity. First, ASSRs can be measured at suprathreshold stimulus levels in ears with significant hearing loss and demonstrate similar amplitudes as normal-hearing individuals (Rodriguez et al, 1986;Vander Werff and Brown, 2005;Leigh-Paffenroth and Murnane, 2011). Second, ASSR amplitudes decrease in the presence of contralateral noise (Maki et al, 2009;Kawase et al, 2012;Kiyokawa et al, 2012;Usubuchi et al, 2014), which may be due at least in part to MOC activity.…”
Section: Introductionmentioning
confidence: 95%
“…There are several reasons why contralateral suppression of ASSRs may be a promising tool for studying MOC activity. First, ASSRs can be measured at suprathreshold stimulus levels in ears with significant hearing loss and demonstrate similar amplitudes as normal-hearing individuals (Rodriguez et al, 1986;Vander Werff and Brown, 2005;Leigh-Paffenroth and Murnane, 2011). Second, ASSR amplitudes decrease in the presence of contralateral noise (Maki et al, 2009;Kawase et al, 2012;Kiyokawa et al, 2012;Usubuchi et al, 2014), which may be due at least in part to MOC activity.…”
Section: Introductionmentioning
confidence: 95%
“…ASSR robustness and synchrony, measured via phaselocking and stimulus-to-response correlations, additionally predicted SIN at a moderate modulation depth of Ϫ4 dB. Notably, ASSR amplitude, which is a common method of quantifying ASSR, was the only ASSR metric that predicted SIN only at a modulation depth of Ϫ8 dB and not at Ϫ4 dB; previous studies using ASSR amplitude as a metric of temporal envelope processing may not have shown relationships be-tween ASSR and SIN if stimulus modulation envelopes were not shallow enough (Guest et al 2018;Leigh-Paffenroth and Murnane 2011). No ASSR metric predicted SIN scores at full modulation (m ϭ 0 dB).…”
Section: Discussionmentioning
confidence: 93%
“…Guest et al (2018) quantified both ASSR amplitude and the change in amplitude with modulation depth and found that neither predicted a difference between listeners with and without SIN difficulties. In two additional studies with both normal-hearing and hearing-impaired listeners, subcortical ASSRs from normal-hearing listeners were not associated with the speech-reception thresholds of masked sentences (Goossens et al 2018) or with word identification in noise and in quiet (Leigh-Paffenroth and Murnane 2011), but ASSRs from hearing-impaired listeners demonstrated a mixed pattern of results: stronger subcortical responses were associated with poorer SIN in Goossens et al ( 2018), but with better SIN in Leigh-Paffenroth and Murnane (2011). Taken together, these studies extend the speech-evoked FFR literature to show that subcortical neural temporal processing relates to SIN perception but provide conflicting findings regarding the precise relationship between sustained envelope encoding and SIN perception.…”
Section: Introductionmentioning
confidence: 97%
“…In the masked condition, one of the seven words was masked by simultaneously playing 20-talker babble at 38 dB (Leigh-Paffenroth & Murnane, 2011). This represents a signal-to-noise ratio (SNR) of +2; a level allowing for generally successful word recognition albeit with perceptual effort.…”
Section: Methodsmentioning
confidence: 99%